The Mystery Of The Pantomime Cat - Blyton, Enid (London Egmont / Eurokids International Ltd, 2011)
The theatre safe has been broken into and boysie. The pantomime cat is top of the list of suspects. But could his friend and fellow actor, Zoe, be the real thief?
Keywords: Children's Literature - Fiction :Detective / Mystery